Monetary integration in the Eurozone and the rise of transnational authoritarian statism. (April 2019) - Schneider, Etienne; Sandbeck, Sune
The negotiations over the Eurozone crisis have increasingly come to reflect Poulantzas' idea of 'authoritarian statism', i.e., a decline in the relevance of democratic institutions and a shift in political power towards technical state apparatuses. Yet, scholarly approaches to transnational integration have provided little guidance as to why monetary relations have become such a pronounced point of condensation for the contradictions inherent in European integration. While mainstream theories of monetary unions such as optimal currency area theory neglect the impact of state power and class interests on monetary politics, more critical perspectives on transnational integration have paid insufficient attention to monetary governance and its role in the mediation of international relations. The present paper brings heterodox theories of international relations and monetary integration to bear on the increasingly authoritarian dynamics of Eurozone governance. Reflecting on Bruff's discussion of authoritarian neoliberalism, we proceed to examine how the circumvention of democratic institutions via Eurozone monetary governance is more precisely captured through the notion of transnational authoritarian statism . We develop this concept in relation to two historical periods of European integration: the formation of the Economic and Monetary Union and the recent extension of the European Central Bank's scope of monetary governance.